Single-dish 1-cm-band radio photometry of protoplanetary discs: few centimetre-sized dust grains?. Issue 3 (30th March 2022) - Greaves, Jane S; Mason, Brian
ABSTRACT: Radio-wavelength observations of protoplanetary discs can show whether large dust grains (pebbles) have formed on the pathway to aggregation of planetary cores. The 100-m Green Bank Telescope was used to make a four-subband (26–40 GHz) photometric survey of the Taurus and Ophiuchus regions, which is nearly complete for class II systems above fixed millimetre-flux thresholds. There is evidence of anomalous microwave emission in 40 per cent of the systems, indicating that radio observations of protoplanetary discs need good spectral coverage to distinguish the presence of dust. At most, one-quarter of the systems are seen to host pebbles, of radii as large as 1 cm. The lack of pebble-dominated systems suggests that this is a short-lived phase in particle size evolution, and/or that pebbles only grow in limited areas of the disc. Either case supports models where grains of centimetre size rapidly fragment and/or drift towards the star, potentially feeding growing planets. In the best-fitting systems, including the 26–40 GHz data raises the detected dust mass by up to an order of magnitude, and the mass distribution of the discs may be flatter. Both of these phenomena could help to solve the 'missing mass' problem, where the solid budget in protoplanetary discs is compared with the substantial requirements of extrasolar-planet systems.